Phanerochaete sordida as a cause of pulmonary nodule in an immunocompromised patient: a case report. Issue 1 (December 2017) - Watanabe, Naoki; Ohkusu, Kiyofumi; Okuda, Masaya; Imataki, Osamu; Ishii, Tomoya; Negayama, Kiyoshi; Tadokoro, Akira; Kita, Nobuyuki; Takagi, Takehiro; Kanaji, Nobuhiro; Kadowaki, Norimitsu; Bandoh, Shuji
Abstract Background Phanerochaete sordida is a species of wood rotting fungus, which can degrade lignin, cellulose and hemicellulose contained in wood and other hard-to-biodegrade organic substances. However, to date, there have been no other reports demonstrating thatP. sordida can infect humans. Case presentation A 66-year-old Japanese man presented for a mass increasing in size on his left thigh. He had been suffering from rheumatoid arthritis for 18 years and chronic obstructive pulmonary disease for 20 years, for which he was being treated with 5 mg/day prednisolone and 8 mg/week methotrexate. The mass resection was performed two months later, and was diagnosed as malignant fibrous histiocytosis. However, a computed tomography examination for tumor recurrence after surgery showed a newly emergent pulmonary nodule. We therefore decided to resect the nodule by thoracoscopic procedure. Histopathological examination of the excised specimen showed that the lesion was a granuloma, with necrotic tissue and clumping ofAspergillus -like hyphae. Therefore, the nodule was diagnosed as a fungal infection and tissue specimens were cultured microbiologically. However, fungal growth was not observed. We consequently performed genetic analysis using a broad-range polymerase chain reaction. The 28S rRNA sequence demonstrated 100% homology withP. sordida using the NCBI BLAST program against the GenBank DNA databases. Conclusions Using broad-range polymerase chain reaction, we identifiedP. sordida as the causative agent of a pulmonary nodule. These findings indicate thatP. sordida may be an additional opportunistic causative organism of pulmonary infection in immunocompromised patients.